1996
DOI: 10.1111/j.1553-2712.1996.tb03379.x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Its Correlates in Emergency Physicians: Four Years' Experience with a Wellness Booth

Abstract: Objective: To measure the degree of burnout among emergency physicians (EPs) and to identify and rank predictive factors. Methods: Using the Maslach Burnout Inventory as well as a 79-item questionnaire, a cross-sectional survey was conducted for physician registrants at the Annual Scientific Assemblies of the American College of Emergency Physicians from 1992 to 1995. Degrees of burnout were stratified into low, moderate, and high ranges. Univariate and stepwise multiple regression analyses were conducted to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
197
8
14

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(232 citation statements)
references
References 26 publications
13
197
8
14
Order By: Relevance
“…There have been few studies in the literature with similar results. [1,9,12,[20][21][22][23][24] Our results also indicated that there was a strong association between burnout and violence experienced by physicians working in emergency departments in our community. Violence-burnout relation in the literature has been referred to as anecdotal so far.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…There have been few studies in the literature with similar results. [1,9,12,[20][21][22][23][24] Our results also indicated that there was a strong association between burnout and violence experienced by physicians working in emergency departments in our community. Violence-burnout relation in the literature has been referred to as anecdotal so far.…”
Section: Discussionsupporting
confidence: 54%
“…[6][7][8] An increased risk of experiencing burnout has previously been linked to a number of factors related to the working environment of the emergency physicians. [1,[9][10][11][12] Certain environmental factors also appear to affect the risk of violence, and these factors are important variables for burnout. [13][14][15] The problem of workplace violence and burnout in the EDs has not been well documented, researched, or managed.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy alone appears lower in hospitalists (3.14 vs 3.27-3.50), possibly because of their often subordinate role with consultants. Hospitalist burnout rates were comparable to those of emergency medicine physicians and internist intensivists 8,9 , but lower than those for surgeons. 36 This study has several limitations.…”
Section: Discussionmentioning
confidence: 73%
“…Other sitebased specialties such as emergency and critical care medicine that share the fast-paced, high-workload, complex care of hospital patients have seen high levels of burnout, which influences job turnover and attrition. 8,9 The first and only large survey of hospitalist demographics and worklife occurred in 1999. 10 Since then, concerns about the sustainability of the specialty grew as reports of burnout, job turnover, and the demand for new hospitalists were common in the specialty newsletters.…”
Section: Introductionmentioning
confidence: 99%
“…In other countries, overcrowding, dealing with patients and families, inadequate administrative support, [17] a higher number of shifts, [18] insufficient personnel and heavy workloads, [19] income and financial matters, malpractice, [20] and familial conflict [21] were significant factors. [22] Besides these factors, the ED was seen as more prone to exhibitions of aggressive behavior, including threatening behavior and verbal and physical attacks.…”
Section: Discussionmentioning
confidence: 99%